Citizenship and morality. (December 2015) - Baron, Jonathan
Abstract : Highlights: I discuss two problems in making democracy work. The failure of citizens to recognize that their participation is more beneficial for others, the wider the circle of others they consider. The failure to think about policy choices in a way that is actively open-minded. Teaching people to avoid these problems might improve the functioning of democratic government. Abstract : I discuss two problems in making democracy work: the failure of citizens to recognize that their participation is more beneficial for others, the wider the circle of others they consider; and the failure to think about policy choices in a way that is actively open-minded. Teaching people to avoid these problems might improve the functioning of democratic government.